Identification of osmotic stress resistance mediated by MdKAI2 in apple - Guo, Hongyang; Chen, Aoxing; Yang, Zhifeng; Yang, Wenmao; Wang, Xianpu; Xu, Lili (Frontiers in Plant Science, 2024)
KAR (Karrikin), a novel plant growth regulator, can be recognized specifically by plants and can activate resistance responses. MdKAI2 is the natural receptor of KARs in apple. Here, we report the identification of osmotic stress resistance in MdKAI2 via genetic transformation. The phenotypic traits, resistance indicators, and transcriptional and metabolic regulation of MdKAI2 were identified. KAR1, a highly active form of KAR, markedly promoted the root growth of Gala cultivar tissue culture-generated plants, possibly through increases in ABA and TZR contents and decreases in the GA3 content. MdKAI2 was markedly upregulated by PEG stress and significantly promoted the growth of apple calli under nonstress conditions, whereas it was significantly inhibited under 20% PEG stress, as was cell death. MdKAI2 significantly increased the content of total flavonoids, the activity of reactive oxygen species (ROS)-scavenging enzymes (SOD, POD and CAT), and the content of osmoregulatory substances (soluble protein, soluble sugars and proline). It also inhibited the MDA content and conductivity under osmotic stress. Differentially expressed genes (DEGs), including multiple transcription factors (TFs), such as MYB, bHLH and AP2-EREBP, are significantly regulated by MdKAI2, and genes involved in the mitogen-activated protein kinase (MAPK) signaling pathway play crucial roles in the regulation of plant resistance. In addition, pathways such as brassinosteroid (BR) biosynthesis and ABC transporters were downregulated, and the MAPK signaling pathway; plant-pathogen interaction; cutin, suberin and wax biosynthesis; alpha-linolenic acid metabolism; and phenylpropanoid biosynthesis were upregulated by MdKAI2. MdKAI2 significantly regulates the levels of lipids, amino acids, terpenoids, benzene, organic acids, carbohydrates, and alkaloids and is involved in the metabolic processes of amino acids, carbohydrates, nucleotides, lipids and secondary metabolites. Furthermore, MdKAI2 positively regulates fatty acids, esters, and terpenoids and negatively regulates metabolites of amino acids, amides and alcohols, and the MAPK signaling pathway may mediate this process.